Inovasi Media Pembelajaran Alat Berat: Prototipe Simulator Excavator Hidrolik Air Berbiaya Rendah Menggunakan Teknologi Fused Deposition Modeling (FDM) - Wibi Pramanda; Barri Zaqi, Sandi Yudha; Utama, Satrio Darma (Jurnal INOVATOR, 2025)
The limitations of physical teaching aids pose a challenge to the effectiveness of learning in the heavy equipment course at Jambi Polytechnic. This study aims to address the issue by designing and building a low-cost excavator simulator prototype as an interactive learning medium. The research method consists of three main stages: component design using FUSION 360, manufacturing with 3D printing technology Fused Deposition Modeling (FDM) using PLA+ material, and assembly of a manual water-based hydraulic system utilizing syringes as actuators. The result is a functional prototype capable of accurately demonstrating all basic excavator movements, including base rotation, as well as boom, arm, and bucket movements controlled through levers. This simulator has proven to be an effective and practical teaching aid solution to enhance students’ practical understanding of mechanical principles and hydraulic systems in heavy equipment.